Marketing Strategy Pariwisata Melalui Marketing Mix Strategy Dan Pengembangan Pariwisata di Kabupaten Lombok Utara (KLU) - Suriadi, Irwan; Supryadi, Didy Ika (Jurnal Ekonomi dan Bisnis, 2017)
This study entitled "Marketing Strategy Through Tourism Marketing Mix Strategy and the development of tourism in north Lombok district (KLU)". The problems of this study were (a) How is the marketing mix of tourism in north Lombok district (KLU) (b) What factors are the strengths, weaknesses, threats and opportunities of tourism development in north Lombok district (KLU), (c ) how is the development of tourism in north Lombok district (KLU), the aim of this study is (a) To analyze how the marketing mix of tourism in Lombok district to the north. (b) what factors are the strengths, weaknesses, threats and opportunities for tourism development in North Lombok regency (c) To formulate tourism development strategy in North Lombok regency. This research is a qualitative research and strategy trying to find a picture pemasarn appropriate tourism in north Lombok district (KLU). The analysis method used in this research is descriptive analysis and SWOT Analisys. The results showed that factors internal strategy (force) that has the main force is the uniqueness in the sights, factors internal strategy (weakness) that has a weakness is the main factor Palayanan to tourists in tourist areas, Opportunity's premier tourist KLU is the layout of the area attractions are located , factor strategy External (threats) which has a main threat is competition tourism intensifies, strategy of tourism development in the KLU is the tourism office at north Lombok district (KLU) must often hold iven-iven tourism in north Lombok district (KLU) and follow ivent sale inside and outside the country.